Rehabilitation of Banana Farms Destroyed by Xanthomonas Wilt in Uganda - Turyagyenda, L.F.; Blomme, G.; Ssekiwoko, F.; Karamura, E.; Mpiira, S.; Eden-Green, S. (J. Appl. Biosci, 2008)
The measures that have been recommended for banana wilt management in Uganda include debudding, disinfection of garden tools and destruction of diseased plants. However, the adoption rate for these options has been low and the disease has reached epidemic levels. Destruction and removal of the infected plants followed by a fallow period or planting of a crop that is not a host of Xcm, and subsequent replanting with healthy banana suckers could restore banana plantations in areas affected by wilt. This study was carried out to determine the most effective method of destroying infected plants and an appropriate fallow period to ensure replanted suckers are not reinfected. Trials were carried out at three field sites with 68-76% of mats infected at the beginning of the experiment. Treatments evaluated were: (1) killing plants by injecting a herbicide (2,4-D) into the pseudo-stems; (2) plants manually cut down and their rhizomes dug out; (3) plants cut down at ground level and re-sprouting suckers continuously mechanically removed. The banana plant debris was piled on ridges between the plots. Replanting with healthy banana suckers started one month after clearing the diseased plants, using tissue culture plantlets of cultivar Pisang Awak and Mpologoma. A portion of the field was replanted each month up to eight months after the onset of the trials. An economic viability analysis of the different options of destroying infected plants was carried out. Banana suckers planted after a one-month fallow period had a 25% survival rate, while all suckers planted after seven and eight months of fallowing survived. Generally, more dead plants were recorded with cv. Mpologoma than cv. Pisang Awak. Incidence of re-infection was highest in the plots where re-sprouting suckers were being continuously removed and lowest in plots where plants had been completely uprooted. A fallow period of at least six months is required to restore health to farms after infection by Xanthomonas wilt. Complete uprooting of infected plants and removing plant debris onto ridges is the best option for managing Xanthomonas wilt. However, the economic viability analysis indicated that farmers preferred to use herbicide to kill the plants rather than uprooting which is more laborious and expensive. The use of herbicide is hence recommended followed by a 6 month fallow or crop rotation period.
Keywords: fallow period; Musa; Xanthomonas wilt; replanting